Carbon Monoxide modulation of neuronal differentiation - Almeida, Ana Sofia Cabral e Sousa de (2016)
Several evidences support carbon monoxide (CO) for modulating cellular differentiation, in particular for neuronal cells. First, there are some reported studies documenting the biogenesis of mitochondria during spontaneous cell differentiation and it was demonstrated that CO promotes mitochondrial biogenesis. Secondly, ROS are signalling molecules in CO-induced pathways and are also key-players in neuronal differentiation. Third, CO has been described as anti-proliferative molecule in different cell types, namely smooth muscle, cancer and T cells, which can be involved in the balance between differentiation and proliferation that occurs during neurogenesis. Therefore, CO presents a strong potential for modulating neuronal differentiation, opening windows for the development of novel cell therapy strategies for neurological disorders.(...)